Substance Use Disorders in Children and Adolescents With Attention-Deficit/Hyperactivity Disorder: Implications for Treatment and the Role of the Primary Care Physician - Upadhyaya, Himanshu P. (Physicians Postgraduate Press, Inc., 2008)
Objectives: Review the association between attention-deficit/hyperactivity disorder (ADHD) and substance use disorder (SUD) in children and adolescents. Discuss treatment implications and the role of the primary care physician in the management of this comorbidity. Data Sources: Articles published from 1991 to 2007 were identified through a MEDLINE search using the search terms attention-deficit/hyperactivity disorder and substance use disorder. Study Selection: Publications cited include reviews of substance use disorders in children and adolescents with ADHD, manuals of diagnostic tests, and 69 studies of substance use disorders in children and adolescents with ADHD. No non–English-language publications were identified. Data Synthesis: Recent reports identify SUD in a high proportion of respondents with ADHD and ADHD in a high proportion of respondents with many types of SUD. Factors that appear to increase the risk for SUD include comorbid psychiatric disorders, particularly conduct disorder. Pharmacotherapy for ADHD appears not to increase the risk for subsequent SUD. Guidelines for the evaluation and treatment of patients with comorbid ADHD and SUD are outlined. Psycho-stimulants carry the risk for misuse by both patients and family members through diversion. Although nonstimulants such as atomoxetine have low abuse potential, they appear to be less efficacious than stimulants. Formulations that have the potential to lower the abuse liability of stimulants are being developed. These include a transdermal form of methylphenidate that has been shown to be efficacious in the treatment of ADHD and a prodrug stimulant, lisdexamfetamine, recently approved for the treatment of ADHD. Clinical data indicate that lisdexamfetamine is efficacious, and significantly lower likability scores were seen with lisdexamfetamine than with equivalent oral doses of d-amphetamine sulfate. Conclusions: Pharmacotherapy may reduce the risk for SUD in patients with ADHD. Psycho-stimulants remain the first-line therapy for the core symptoms of ADHD. New formulations of pharmacologic agents with a reduced potential for abuse are being developed.